Reconstruction of Pesantren Literature Through A. Mustofa Bisri’s Short Story Collection - Lamri Lamri; Bilqis Salsabila Safa; Leonita Leonita; Moh. Khalid Hasan (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The term